Towards a System of Multilateral Unit Labor Cost-Based Competitiveness Indicators for Advanced, Developing, and Transition Countries - Turner, Anthony (IMF Working Papers; Working Paper ;, 1997)
This paper attempts to extend the range of countries covered by the IMF's multilateral real exchange rate indexes based on relative unit labor costs (REER-ULCs) in manufacturing. A data set was assembled that permits calculation of REER-ULCs for 23 newly industrialized, developing, and transition countries in addition to the 21 industrial countries covered by the current system. Although the results are mostly quite encouraging, they should be considered preliminary because of uncertainty about the reliability and comparability of the underlying data. Also, unit labor costs are not available on as timely a basis as consumer price indexes (CPIs), especially for nonindustrial countries. Thus, the ULC-based indicators should supplement rather than replace the current CPI-based system.